Stroke prophylaxis after US emergency department diagnosis and discharge of patients with atrial fibrillation and flutter from 21 hospitals - Bory Kea; E. Margaret Warton; Candice E. Kutz; Erin Kinney; Dustin W. Ballard; Mary E. Reed; Gregory Y. H. Lip; Merritt Raitt; Benjamin C. Sun; David R. Vinson; on behalf of the KP CREST Network (International Journal of Emergency Medicine)
Abstract Background Oral anticoagulation (OAC) reduces stroke and mortality risk in patients with non-valvular atrial fibrillation/flutter (AF). Patterns of OAC initiation upon discharge from US emergency departments (ED) are poorly understood. We sought to examine stroke prophylaxis actions upon, and shortly following, ED discharge of stroke-prone AF patients. Methods We included all adults with a primary diagnosis of non-valvular AF, high stroke risk (CHA2DS2-VASc ≥ 2), low/intermediate bleeding risk (HAS-BLED < 4), and no recent (< 90 days) OAC at discharge from 21 community EDs (2010–2017). Annual rates of appropriate stroke prevention action (OAC Action) were calculated for eligible discharges and as defined as an OAC prescription or anticoagulation management service consultation within 14 days of ED discharge. We modeled OAC Action using a parsimonious Poisson regression with identity link adjusting for sex, age, race/ethnicity, stroke risk score (CHA2DS2-VASc), year of visit, provider race/ethnicity, number of ED beds, and presence of an outpatient observation unit, with the patient as a random effect. Results We studied 9,603 eligible ED discharges (mean age 73.1 ± 11.4 years, 62.3% female), and mean CHA2DS2-VASc score 3.5 ± 1.5. From 2010 to 2017, OAC Action increased from 21.0% to 33.5%. Factors associated with lower OAC initiation included the following: female sex (-3.6%, 95% CI -5.4 to -1.9), age ≥ 85 vs < 64 years (-3.8%, 95% CI -6.7 to -1.0%), ED beds, n = 20 to 29 (-5.3%, 95% CI -8.36 to -2.4%), 30–49 (-3.8, 95% CI -6.5 to -1.2%), and 50 + (-7.1%, 95% CI -10.6 to -3.7%); with referent being the male sex, < 40 years, and fewer than 20 beds (18.1%, 95% CI 12.8 to 23.4). OAC initiation in 2017 was greater than in 2010 (16.0%, 95% CI 12.3 to 19.7%). Conclusion Within a community-based ED population of AF patients at high stroke risk, rates of appropriate stroke prevention action increased over the 7-year study period. Rates of AF thromboprophylaxis may be improved by addressing sex and age disparities, as females and those age ≥ 75 were less likely to receive indicated stroke prevention.